Widow Empowerment Model in Sumenep Regency: Constructing Financial and Non-Financial Approaches for Economic Independence - Zuhri, Ach. Zuhri (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
This study aims to develop a model for empowering widows in Sumenep Regency through financial and non-financial approaches to increase economic independence. The research background is based on the fact that widows are a vulnerable community facing multiple barriers in the form of limited access to capital, financial literacy, business skills, and social stigma. This study uses a mixed methods method, where the initial qualitative stage was conducted through in-depth interviews with community leaders, members, academics, community leaders, and local government officials, which were analyzed using Atlas.ti to map key thematic issues. Next, the conceptual model was tested quantitatively using Structural Equation Modeling-PLS (SEM-PLS) on 94 respondents from the Great Widow Community out of a total population of 220 people. The analysis results show that non-financial interventions (skills training, social support, digital literacy, and networking) have a significant effect on empowerment and economic independence, while financial interventions only have a direct effect on economic independence, but not significantly on empowerment. This finding confirms that empowerment plays an important mediating mechanism, particularly in linking non-financial interventions to economic outcomes. This study provides theoretical contributions by emphasizing the importance of integrating financial and non-financial approaches in the empowerment model for vulnerable women, as well as practical contributions for policymakers and community empowerment institutions in designing more sustainable and contextual programs